Cytokine-Enhanced Vaccine and Suicide Non-Viral Gene Therapy in Advanced Metastatic Melanoma Patients: Two Case Reports - Finocchiaro, Liliana Maria Elena (2020)
The prognostic for metastatic melanoma is very poor when treated with standard cytotoxic chemotherapies and it is often refractory to check point inhibitors and/or molecular targets. In this context the development of new treatments with better efficacy and safety profiles is highly desirable. Based on our successful experience applying suicide and immune gene therapy in a veterinary clinical setting, we are proposing its translation to human patients. We are presenting here the first-in-human safety assay of this approach. We report two cases of refractory metastatic melanoma. The first-one was a 27-years-old pharyngeal mucosal melanoma patient with a primary tumor in his left tonsil. Despite transient slowing down, the disease successively progressed to radiotherapy, radical surgery, ipilimumab, nivolumab, imatinib and temozolomide. The second-one was a 72-years-old malignant melanoma patient with a primary tumor in his left hallux. Despite transient slowing down, the disease successively progressed to hallux amputation, inguinal lymphadenectomy, radiotherapy, interferon-alpha, ipilimumab, pembrolizumab and temozolomide. The proposed treatment included local intratumoral suicide gene therapy concomitant with a subcutaneous vaccine composed by allogeneic tumor extracts and liposomes with plasmids bearing IL-2 and GM-CSF genes. The treatment was safe: the only side effects were from mild to moderate and manageable: pyrexia, swelling of the injected tumor and partial hair loss (alopecia). Due to disease progression both patients were withdrawn from the study before completing the complete series of interventions. These preliminary data encourage the completion of further clinical trials to establish the possible clinical benefit of the proposed approach.